2008
DOI: 10.1142/s021773230802971x
|View full text |Cite
|
Sign up to set email alerts
|

YN CORRELATIONS FROM THE STOPPED K REACTION ON 4He

Abstract: We have investigated correlations of coincident ΛN pairs from the stopped K − reaction on 4 He, and clearly observed Λp and Λn branches of the two-nucleon absorption process in the ΛN invariant mass spectra. In addition, non-mesonic reaction channels, which indicate possible exotic signals for the formation of strange multibaryon states, have been identified.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 18 publications
3
26
0
Order By: Relevance
“…The region corresponding to larger Λp invariant masses contains the third process -direct Λ production after a double nucleon absorption of K − on two protons. A similar explanation was proposed by the KEK collaboration in [10]. Other possible processes which could contribute to the spectra should be investigated too.…”
Section: Pos(bormio2014)013supporting
confidence: 58%
See 1 more Smart Citation
“…The region corresponding to larger Λp invariant masses contains the third process -direct Λ production after a double nucleon absorption of K − on two protons. A similar explanation was proposed by the KEK collaboration in [10]. Other possible processes which could contribute to the spectra should be investigated too.…”
Section: Pos(bormio2014)013supporting
confidence: 58%
“…Until now several experiments presented their results, but the interpretation is not conclusive, so the puzzle remains unsolved. Two main experimental approaches have been used in the search for K − pp clusters: p-p and heavy ion collisions, as, for example, in the DISTO experiment [8] and a low momentum or stopped K − interactions in light nuclei, as in the FINUDA [9] and KEK-PS E549 [10] experiments. The second approach is used also in our experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently new experiments were performed with these features. KEK-E549 performed a high statistics K − 4 He absorption experiment [8,9] and was able to effectively separate, by means of the missing mass method, several reactions contributing to the observed (ΛN) final state. While the K − 4 He → Σ(3N) followed by Σ conversion and K − 4 He → ΛN(2N) could give signatures in the missing mass spectra that had an exactly localizable counterpart in the (ΛN) invariant mass ones, the central (and largest) part of the latter could not be explained as easily.…”
Section: K − Absorption: General Overviewmentioning
confidence: 99%
“…Complementary information can also be provided by the study of the missing mass distributions, as demonstrated by the E549 analyses [8,14], which help identifying phase-space regions exclusively populated by defined reactions. Applying this method also to FINUDA data (considering for instance the lightest available target, 6 Li), the results obtained are basically in agreement with E549 issues, concerning both Λp and Λd final states.…”
Section: K − Absorption: General Overviewmentioning
confidence: 99%
“…Also the E549-KEK experiment [17,18] studied the Λp and Λn pairs from the 4 He(K − stop , ΛN)X reaction. The low mass of the system and an analysis in terms of invariant and missing mass variables allow to get a deeper under- Exclusive and possibly complete measurements of the K − absorption events are evidently the way to go to understand the K − absorption dynamics and possibly identify deeply bound kaonic clusters.…”
Section: Introductionmentioning
confidence: 99%